Scientists' opinion, attitudes, and consensus towards immunity passports - Iván Aranzales; Ho Fai Chan; Reiner Eichenberger; Rainer Hegselmann; David Stadelmann; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2021)
We designed and implemented a survey to capture what scientists from around the world think about immunity certification. Responses from 12,738 scientists were captured and their distribution was tabulated by participants in health science and other fields. Half of the scientists surveyed agree that a potential immunity passport program will be good for public health (50.2%) and the economy (54.4%), with 19.1% and 15.4% of participants disagree, respectively. A significant proportion of scientists raised concerns about immunity certification over fairness to others (36.5%) and social inequality (45.5%). There is little consensus in the different aspects of immunity passport among scientists.
Keywords: 330